PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DI LEMBAGA PEMASYARAKATAN KELAS IIA MANADO - Sandy Kristian Mamuaya; Joyce Jacinta Rares; Weliam Agustinus Areros (Sam Ratulangi University, 2021)
This study aims to determine the effect of leadership and work motivation on the performance of state civil servants. This research was started from July to November 2020 at the Correctional Institution Class IIA Manado. The population in this study was all State Civil Servants (ASN) in the Correctional Institution Class IIA Manado They were 100 respondents and this population was the sample in this study. Data collection techniques in this study using a questionnaire. Data analysis techniques used normality test, heteroscedasticity test, and multiple linear regression analysis. The results showed that, the first, leadership has a positive effect on the performance of the State Civil Service in Correctional Institution Class IIA Manado with a regression coefficient value of 0.034, so that the better the leadership, the better the performance of the State Civil Apparatus. Second, work motivation has a positive effect on the performance of the State Civil Apparatus in Manado Class IIA Penitentiary with a regression coefficient value of 0.742, so that the better the work motivation, the better the performance.